The Next Generation of Personalized Medicine: A Comprehensive Review (International Journal of Scientific Research in Science and Technology, 2025)
The pharmaceutical sector is nevertheless confronted with formidable obstacles. These days Drug research and the advancement of healthcare systems are two areas in which personalized medicine is significantly contributing. Personalized medicine, also known as precision medicine. The basic principle of personalized medicine is that the appropriate drug should be administered to the appropriate patient at the appropriate time for the appropriate period of time. The approach depends on gathering clinical, genetic, and epigenomic data that improves our comprehension of how an individual's distinct genomic inventory contributes to particular diseases. The current standard in the field of specific medication therapy is protein medicines. They are more effective in regulating the biological processes connected to disease because they have better biological activity and target specificity than small molecule pharmacological medications. They also hold great promise for the creation of personalized drugs. As proteoformics research progresses, personalized medication therapy—particularly specific protein medications that target proteoforms as a drug target will advance knowledge of disease mechanisms, identify new drug targets and signalling routes, offer a theoretical foundation for the creation of new medications, assist physicians in performing evaluations of health risks and developing more affordable targeted prevention strategies using AI and machine learning, foster innovation in technology, and offer more convenient treatment based on a The distinct profile of the patient, all of which will be advantageous to both the affected people and the community at large. This strategy is a full continuation of the advanced method for improving our capacity to forecast which medical interventions will be secure and successful for each patient.
Keywords: Personalized medicine; Challenges; Genomes; targeted therapy; proteoforms; proteoformics